Impact of Economic Growth and Exchange Rate Volatility on FDI Inflows: Cointegration and Causality Tests for the BRICS Countries - Elian, Mohammad I.; Bani-Mustafa, Ahmed; Sawalha, Nabeel; Alsaber, Ahmad R.; Pan, Jiazhu (International Journal of Economics and Financial Issues, 2024)
This paper examines impact of economic growth, exchange rate volatility, and the real exchange rate on Foreign Direct Investment (FDI) inflows to BRICS economies. We employed the cointegration testing to investigate the long-term relationship between the selected regressors and Granger Non-Causality test to analyze the direction of causality between variables. Diagnostic tests were conducted to check serial correlation in our model and to detect model misspecification. The stability of parameters at a 5% significance is graphically presented. The results indicate that economic growth is a positive significant determinant of FDI inflows in both the short and long term, and exchange rate volatility and the real exchange rate have a negative insignificant impact on FDI inflows in the short run, with the exchange rate showing a positive significant link in the long run. The relationships with control variables are mixed: the coefficients of gross fixed capital formation display a positive and significant relationship with FDI inflows in the short run, but an insignificant one in the long run. Trade openness and inflation demonstrated an insignificant link to FDI inflows, while GDP per capita had a positive significant impact in both terms. These findings offer valuable insights for policy reforms and economic integration across countries.